PENGEMBANGAN MEDIA ANIMASI MENGGUNAKAN ADOBE FLASH SEBAGAI MEDIA PEMBELAJARAN IPA PADA MATERI SISTEM PERNAPASAN KELAS VIII SMP - Reni Wulandari; Zulfarina Zulfarina; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrat : The progress of Information and Communication Technology (ICT) in the21st century enables the automation of almost all fields, including education, necessary forrenewal, improvement and development of the education system in learning that can not beseparated from the activities of teachers and students in the learning process.Biologymaterial that discusses physiology is very difficult for students to understand because it isabstract. An alternative used to facilitate students is to utilize applications or software inmaking media, one of them is Adobe Flash software in making animation media. This studyaims to develop and produce animated media using Adobe Flash which is valid as ascience learning medium on the Respiratory System class VIII SMP. This type of researchused in this study is research and development (R&D) using the Four-D model. The resultsof the media validation are very valid with an average score of 3.74. The results of smallgroup trials on animated media using adobe flash that were developed were very good witha score of 98.75 while the results of the field trials of animated media using adobe flashwere very good with a score of 94.68 and could be applied in classroom learning activities.Keywords: Animation media, Adobe Flash, Four-D